2019
DOI: 10.2217/imt-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

Validation of immunogenic PASD1 peptides against HLA-A*24:02 colorectal cancer

Abstract: Colorectal cancer is the third commonest malignancy in Asia including Malaysia. The immunogenic cancer-testis antigens, which are expressed in a variety of cancers but with limited expression in normal tissues except the testis, represent an attractive approach to improve treatment options for colorectal cancer. We aimed to validate four PASD1 peptides as the immunotherapeutic targets in colorectal cancer. First, PASD1 mRNA and protein expression were determined via real-time polymerase chain reaction (RT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…This current study shows the highest PASD1 protein expression in the CRC population (31.7%). A previous study described only 17.4% PASD1 expression in CRC ( Soh et al, 2019 ). The possible reason for these discrepancies was the PASD1 antibodies used in both studies.…”
Section: Discussionmentioning
confidence: 93%
“…This current study shows the highest PASD1 protein expression in the CRC population (31.7%). A previous study described only 17.4% PASD1 expression in CRC ( Soh et al, 2019 ). The possible reason for these discrepancies was the PASD1 antibodies used in both studies.…”
Section: Discussionmentioning
confidence: 93%
“…[ 36 ] PASD1 is an immunogenic protein in colorectal cancer that encourages cell proliferation in glioma cells. [ 37 38 ] In gastric cancer patients, this protein is up-regulated, and this up-regulation has a relationship to OS.…”
Section: Discussionmentioning
confidence: 99%
“…e combination of traditional treatment methods with immune checkpoint inhibitors could provide promising treatment strategies for cancer patients, including CRC [38]. Numerous studies have shown that immunotherapy can inhibit the growth of colorectal cancer cells and prolong the survival period of patients [39][40][41]. In this paper, the correlation between PIGR and immune-associated signatures was explored by comprehensive bioinformatic technologies.…”
Section: Discussionmentioning
confidence: 99%